2018
DOI: 10.1002/jlb.3a0917-368r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Mer receptor tyrosine kinase inhibition of glomerular endothelial cell inflammation

Abstract: Endotoxin induces a variety of proinflammatory mediators and plays a crucial role in kidney inflammation. The receptor tyrosine kinase, Mer, diminishes renal inflammation by attenuating inflammatory responses. We previously reported that Mer is predominantly expressed on glomerular endothelial cells (GECs) and that Mer deficiency is associated with increased renal inflammation when mice are challenged with nephrotoxic serum. We consequently hypothesized that Mer signaling down-regulates LPS-driven inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Axl activation leads to marked suppression of Ifn mRNA in mice injected with anti-Axl antibodies [23], and similar inhibition was also observed in DCs when Axl is activated by Gas6 [7]. Mer was found to be highly expressed on endothelial cells in mouse kidneys [33]. We found that Mer activation leads to the suppression of LPS signaling in primary glomerular endothelial cells through the upregulation of SOCS3 but not SOCS1 [33].…”
Section: Tam Signaling Pathways and Immunobiological Functions: Immentioning
confidence: 56%
See 1 more Smart Citation
“…Axl activation leads to marked suppression of Ifn mRNA in mice injected with anti-Axl antibodies [23], and similar inhibition was also observed in DCs when Axl is activated by Gas6 [7]. Mer was found to be highly expressed on endothelial cells in mouse kidneys [33]. We found that Mer activation leads to the suppression of LPS signaling in primary glomerular endothelial cells through the upregulation of SOCS3 but not SOCS1 [33].…”
Section: Tam Signaling Pathways and Immunobiological Functions: Immentioning
confidence: 56%
“…Mer was found to be highly expressed on endothelial cells in mouse kidneys [33]. We found that Mer activation leads to the suppression of LPS signaling in primary glomerular endothelial cells through the upregulation of SOCS3 but not SOCS1 [33]. Axl expression in mesangial cells is promoted largely by transcription factor Sp1, but not Sp3.…”
Section: Tam Signaling Pathways and Immunobiological Functions: Immentioning
confidence: 99%
“…A series of papers by Zhen, Shao, and colleagues show that MERTK is expressed on glomerular endothelial cells and it downregulates renal inflammation induced by nephrotoxic serum [6567]. They identified several mechanisms through which MERTK tames inflammation, such as suppressing Stat1 and Stat3 expression, reducing ERK1/2 and Akt activation, inhibiting NF- k B, and promoting SOCS3 expression [66]. These scattered reports in different organs and inflammatory processes come together with our studies to suggest that endothelial MERTK regulates inflammatory processes and endothelial repair.…”
Section: Discussionmentioning
confidence: 99%
“…TAM receptors are essential regulators of immune homeostasis by the recognition and phagocytosis of PS-exposing apoptotic cells via their ligands Gas6 and Protein S [44]. In addition, all 3 TAM receptors are able to promote other cellular functions, such as cell survival, through mechanisms involving, for example, the PI3K/Akt or ERK1/2 signaling pathway or proliferation and migration [45], and they were shown to be expressed in endothelial cells [41,42,46]. Taken together, the impact of Gas6 on the individual TAM receptors either acting cooperatively or by distinct signaling pathways on diverse functions of angiogenesis needs to be further addressed.…”
Section: Discussionmentioning
confidence: 99%